The Divine Legal Discourse of the Temple Scroll: Space, Time, and Presence - Zahn, Molly M. (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2025)
One of the most notable features of the Qumran Temple Scroll is its self-presentation as direct divine speech. This essay argues that the scroll’s divine voice communicates much more than a simple authority claim; instead, the divine voicing is fundamental to the larger aims of the composition, in two specific ways. First, it communicates an essentially priestly theology of God’s presence. Second, God’s legal discourse functions as part of a comprehensive effort to instantiate the composers’ utopian image of sacred space in their audience’s minds. By avoiding nearly all mention of history, the Temple Scroll keeps the focus resolutely on the imagined temple space created by its legal discourse. The very few exceptions to this avoidance of history illustrate how the scroll’s composers negotiated the tension between their image of a perfect, enduring sanctuary commanded at Sinai and the legacies of exile and foreign domination that marked their Second Temple reality.